Empowering women through land rights - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Command over property is arguably the most severe form of inequality between men and women today. Despite their prevalence, gender differences in rights to land are some of the most poorly documented dimensions of gender inequality and figure in few statistical systems. Land rights increase women's power in social, economic, and political relationships. Rural women claim that secure land rights increase their social and political status, and improve their sense of self-esteem, confidence, security, and dignity. These rights can also increase women's bargaining power in their families and participation in public dialogue and local political institutions.